Perlindungan Hukum Terhadap Konsumen Pemakai Air PDAM Atas Pelayanan Yang Merugikan Konsumen: (Studi Di Kota Mataram) - Nunuk Ieka Juliana Sari; H. Djumardin Djumardin (Private Law, 2022)
This research has the purpose to find out the right and duty regulations in the PDAM Mataram agreement that make damages for customers, and find out the type of legal protections against customers who got damages by the services of PDAM Mataram City. This research uses normative-empirical legal research. The consumer's legal protection against water services by PDAM that make damages for the customers, namely the legal protection on their agreement on the implementation uses written on their form. This form is about rights and duties the parties regulate in Act Number 8 of 1999 about consumer protection. The type of legal protection against customers for water services by PDAM Mataram City that makes damages for the customers, namely if they break the consumer's rights so the customers can use the provisions as stipulated in Act Number 8 of 1999 concerning Consumer Protection to make a lawsuit. Meanwhile, lawsuits against the business actors, namely the PDAM Kota Mataram, can be imposed through civil, criminal, or state administrative law process.